2014
DOI: 10.1089/aid.2013.0144
|View full text |Cite
|
Sign up to set email alerts
|

Relatively High Prevalence of Drug Resistance Among Antiretroviral-Naive Patients from Henan, Central China

Abstract: To elucidate the prevalence of HIV-1 subtypes and transmitted drug resistance in Henan, central China, HIV-1-positive blood samples from 187 antiretroviral-naive patients were collected in our study from August 2009 to November 2010. Subtype B¢ (92.0%, 172 of 187) remains the predominant HIV-1 subtype in Henan province and was prevalent in all risk populations and geographic regions. Of 98 pol sequences 67 (68.4%) harbored drug resistance mutations, and only 14 (14.3%, 14 of 98) sequences have mutations associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Another study from Guangdong province showed that the prevalence of TDR was 6.7% after 5 years of the scale-up [20]. A report from Henan province, the first province to provide free ARV to HIV-infected individuals in 2003 in China, shows that the prevalence of TDR in the province is 14.3%, 8 years after the scale-up [21]. The difference in the prevalence of TDR between Guangxi and Henan provinces is significant (χ 2 = 13.178, p < 0.001), although the period from scale-up to sample collection is the same.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Guangdong province showed that the prevalence of TDR was 6.7% after 5 years of the scale-up [20]. A report from Henan province, the first province to provide free ARV to HIV-infected individuals in 2003 in China, shows that the prevalence of TDR in the province is 14.3%, 8 years after the scale-up [21]. The difference in the prevalence of TDR between Guangxi and Henan provinces is significant (χ 2 = 13.178, p < 0.001), although the period from scale-up to sample collection is the same.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, we found a distinct clustering of Chinese subtype B strains (GenBank accession numbers KC988120-KC988159 23 ) from those from South Korea in phylogenetic analysis and none of our K103N TDR strains was genetically related to the Chinese subtype B strains (data not shown). Therefore, we believe that the increasing prevalence of K103N TDR is likely a consequence of the widespread use of NNRTI in South Korea in the past decade as observed in other areas.…”
mentioning
confidence: 67%
“…However, the high cost of whole-genome sequencing has limited its usage, and thus sequencing of focused genomic regions, such as the Gag, Pol, Env, and Vpr genes or a combination of different gene fragments, is viewed as a relatively cost-effective alternative (Preston et al, 1988;Mansky and Temin, 1995;Lan et al, 2008;Chen et al, 2011;Chen et al, 2012). Three structural genes (Chen et al, 2011) [Gag (Yao et al, 2012;Ye et al, 2012), Env (Pang et al, 2012;Ye et al, 2012;Li et al, 2014a) and Pol (Holguín et al, 2008;Chen et al, 2014;Yan et al, 2015)] have been widely used for genotyping HIV. Previous studies led to the classification of HIV into two main types, HIV-1 and HIV-2 (Zhang et al, 2015), with HIV-1 being the predominant branch.…”
Section: Infection With Human Immunodeficiency Virus (Hiv) Typically mentioning
confidence: 99%
“…For example, one patient was reported to be infected with subtype C based on sequencing of the Pol gene and the p17 fragment of Gag gene; however, the same individual was classified as CRF07_BC with the p24 fragment of the Gag gene, as well as subtype B with the Vpu gene (Robertson et al, 2000;Chen et al, 2013). To avoid such discrepancies, simultaneous analysis of different gene fragments, such as Gag/Env Chen et al, 2013), Gag/Pol (Yao et al, 2012), Pol/Env (Chen et al, 2012;Pang et al, 2012), and Gag/Pol/ Env (Lan et al, 2008;Ye et al, 2012;Zeng et al, 2012;Li et al, 2014a;Dai et al, 2015), will facilitate the clear identification of potential new inter-subtype recombinants. However, the field still lacks a set of standard markers for identifying HIV strains, which precludes inter-study comparisons and hampers the comprehensive understanding of the panorama of HIV infection.…”
Section: Infection With Human Immunodeficiency Virus (Hiv) Typically mentioning
confidence: 99%
See 1 more Smart Citation